2016
DOI: 10.2987/moco-32-02-117-123.1
|View full text |Cite
|
Sign up to set email alerts
|

New Candidates for Plant-Based Repellents AgainstAedes aegypti

Abstract: Based on an ethnobotanical study on use for plant species against mosquito bites in the Kota Tinggi District, Johor State, Malaysia, 3 plants selected for study, Citrus aurantifolia (leaves), Citrus grandis (fruit peel), and Alpinia galanga (rhizome), were extracted using hydrodistillation to produce essential oils. These essential oils were then formulated as a lotion using a microencapsulation process and then tested for their repellent effect against Aedes aegypti. N,N-diethyl-m-toluamide (deet) was also pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 18 publications
0
5
0
2
Order By: Relevance
“…While this quality can be considered valuable for their potential risk to the environment or individuals, it may also be considered a hurdle that must be overcome in the identification and deployment of long-lasting repellent technologies. Surfaces treated with various plant compounds were in some cases no longer capable of producing appreciable repellency after 30 min [73]. This represents a need for improvement in the repellency of these various botanical compounds.…”
Section: Current and Future Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…While this quality can be considered valuable for their potential risk to the environment or individuals, it may also be considered a hurdle that must be overcome in the identification and deployment of long-lasting repellent technologies. Surfaces treated with various plant compounds were in some cases no longer capable of producing appreciable repellency after 30 min [73]. This represents a need for improvement in the repellency of these various botanical compounds.…”
Section: Current and Future Technologiesmentioning
confidence: 99%
“…Among this class of compounds, two types of terpenoids appear to be highly efficacious at repelling arthropods: monoterpenoids and sesquiterpenoids. Paluch et al demonstrated that various sesquiterpenoids were highly effective at repelling yellow fever mosquitoes in a static air chamber designed for monitoring spatial repellency, and in other studies identified numerous monoterpenoids that were capable of repelling a large variety of arthropod pest species [73,74,77]. While many of these compounds are successful repellents, their residual character on treated surfaces is quite low.…”
Section: Current and Future Technologiesmentioning
confidence: 99%
“…aegypti adult [29]. Abdullah et al [1] reported antifeedant, repellent and toxic effects of A. galanga rhizomes on Coptotermes gestroi and Coptotermes curvignathus.…”
Section: Discussionmentioning
confidence: 99%
“…It exhibited >98% repellent effect for the duration of 4 h, whereas, in the field conditions, these formulations demonstrated the comparable repellent effect (100% for a duration of 3 h) to Citriodiol®-based repellent (Mosiguard®). In both test conditions, the microencapsulated formulations of the EOs presented longer duration of 100% repellent effect (between 1 and 2 h) than non-encapsulated formulations [80]. Microencapsulation reduces membrane permeation of CO while maintaining a constant supply of the citronella oil [81].…”
Section: Conclusion and Challenges For Future Researchmentioning
confidence: 93%